A new genus and new species assigned to Macrophthalmidae (Decapoda: Brachyura: Thoracotremata) from the Ryukyu Islands, Japan - Komai, Tomoyuki; Fujita, Yoshihisa (Zootaxa, 2018)
Mirograpsus asper is described as a new genus and new species in the subfamily Ilyograpsinae Števčić, 2005, of the family Macrophthalmidae Dana, 1851, on the basis of a single male specimen from Ishigaki Island, Ryukyu Islands, Japan. The new genus most closely resembles the monotypic Apograpsus Komai & Wada, 2008 (type species, Ilyograpsus paantu Naruse & Kishino, 2006), sharing a similar carapace shape, but is differentiated chiefly by the fusion of the male pleomeres 4–6 and the unarmed meri of the ambulatory legs. The functional fusion of the male pleomeres 4–6 is unique in the Macrophthalmidae.